Application of Physical-Chemical Approaches for Encapsulation of Active Substances in Pharmaceutical and Food Industries - Řepka, David; Kurillová, Antónia; Murtaja, Yousef; Lapčík, Lubomír (Foods (Basel, Switzerland), 2023)
BACKGROUND: Encapsulation is a valuable method used to protect active substances and enhance their physico-chemical properties. It can also be used as protection from unpleasant scents and flavors or adverse environmental conditions. METHODS: In this comprehensive review, we highlight the methods commonly utilized in the food and pharmaceutical industries, along with recent applications of these methods. RESULTS: Through an analysis of numerous articles published in the last decade, we summarize the key methods and physico-chemical properties that are frequently considered with encapsulation techniques. CONCLUSION: Encapsulation has demonstrated effectiveness and versatility in multiple industries, such as food, nutraceutical, and pharmaceuticals. Moreover, the selection of appropriate encapsulation methods is critical for the effective encapsulation of specific active compounds. Therefore, constant efforts are being made to develop novel encapsulation methods and coating materials for better encapsulation efficiency and to improve properties for specific use.
Keywords: encapsulation; pharmaceutical; food; physico-chemical properties